METHODS OF SPEECH DEVELOPMENT OF STUDENTS IN PRIMARY CLASSES - Abduvaliyeva Nodira Alisherovna; Khalimjonova Irodakhon Uktamjon kizi (Zeta Repository, 2023)
This article focuses on the effective organization of mother tongue and reading literacy classes in primary school. First of all, it is necessary to improve the literacy of the native language and reading in the study of a number of features, such as correct reading, increasing vocabulary, teaching broad thinking, improving speech, consciousness. should be able to form.